Suggestions for telecom operators’ big data development - Yunyong ZHANG (Dianxin kexue)
The development of big data at home and abroad was reviewed.On the basis of carefully analyzing the background,advantages and current situation of the development of big data,it was thought that the further development of telecommunication big data was the main component of promoting the national big data strategy project,and suggestions to promote the deepening development of telecom operators’ big data was proposed.